Pengaturan Larangan Plastik Sekali Pakai: Kritik Terhadap Putusan Mahkamah Agung Nomor 29 P/Hum/2019 Dari Perspektif Teori Dan Hukum Perundang-Undangan - Umbu Rauta; Titon Slamet Kurnia (Fakultas Hukum Universitas Islam Indonesia, 2021)
This article discusses the Supreme Court Decision Number 29 P/HUM/2019 on the Judicial Review of Article 7 and Article 9 paragraph (1) of Governor of Bali Regulation No. 97 of 2018 on Restrictions on the Generation of Single-use Plastic Waste. The Supreme Court (MA) rejected the applicant's application with a dedicendi ratio that the a quo Governor's Regulation was justifiable as it was based on the principle of decentralization and the impact of single-use plastic waste that pollutes or damages the environment. The legal issues highlighted relate to how the relationship between legal products in the form of legislation and regulations should be, as well as whether the Supreme Court's judicial considerations in its decisions are appropriate according to the law. The research method is done with conceptual and case study approaches. The results of the study that: First, legal products in the form of regulations are an elaboration of legislation, so that regulations may not create new legal norms. Second, the Supreme Court's judicial opinion is incorrect as it does not distinguish between legislation and regulation products, so there is an impression that everything can be regulated by regional legal products provided that it is in accordance with the regional conditions. In addition, the act of limiting Human Rights is only carried out through legislative products in the form of legislation (laws).